(untitled) (Research, Society and Development, 2021)
The home environment is seen as the main factor influencing child development. We can understand the Affordance as a set of opportunities that provide challenges to individual development. The aim of this study was to verify the motor opportunities levels (affordances) of children living at home or apartment. Transversal descriptive study included a sample of 49 volunteer tutors of children of both sexes aged between 18-42 months. The instrument used to evaluate the level of opportunities for children’s motor development was the questionnaire Affordances in the Home Environment for Motor Development (AHEMD – 18-42 months). After applying the questionnaire, collected data were entered and classified with the help of an application in Microsoft Excel program (AHEMD Calculador VPbeta1.5.xls). The house had significantly higher values compared to the apartment environment except in the materials of fine and gross motor skills. We believe that children living in houses have greater motor opportunities in relation to children residing in apartments, which may reflect the children’s motor development throughout childhood.